2016
DOI: 10.1016/j.jconrel.2016.09.023
|View full text |Cite
|
Sign up to set email alerts
|

In vitro potency, in vitro and in vivo efficacy of liposomal alendronate in combination with γδ T cell immunotherapy in mice

Abstract: Nitrogen-containing bisphosphonates (N-BP), including zoledronic acid (ZOL) and alendronate (ALD), have been proposed as sensitisers in γδ T cell immunotherapy in pre-clinical and clinical studies. Therapeutic efficacy of N-BPs is hampered by their rapid renal excretion and high affinity for bone. Liposomal formulations of N-BP have been proposed to improve accumulation in solid tumours. Liposomal ALD (L-ALD) has been suggested as a suitable alternative to liposomal ZOL (L-ZOL), due to unexpected mice death ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 60 publications
2
41
0
Order By: Relevance
“…Using an ovarian tumour model established by intraperitoneal (IP) inoculation, liposomal alendronate (L-ALD) has been shown to be more effective at slowing tumour growth than ALD when administered intravenously in combination with Vγ9Vδ2 T cells that were injected into the peritoneal cavity of mice [9]. Additionally, we have recently reported that only the combinatory treatment of L-ALD and γδ T cells led to a significant reduction in tumour growth in the experimental metastatic lung melanoma model, after 3 successive intravenous injections [20,21].…”
Section: Ivyspringmentioning
confidence: 99%
See 4 more Smart Citations
“…Using an ovarian tumour model established by intraperitoneal (IP) inoculation, liposomal alendronate (L-ALD) has been shown to be more effective at slowing tumour growth than ALD when administered intravenously in combination with Vγ9Vδ2 T cells that were injected into the peritoneal cavity of mice [9]. Additionally, we have recently reported that only the combinatory treatment of L-ALD and γδ T cells led to a significant reduction in tumour growth in the experimental metastatic lung melanoma model, after 3 successive intravenous injections [20,21].…”
Section: Ivyspringmentioning
confidence: 99%
“…Lipid stock solutions were prepared in chloroform/methanol (4:1 v/v) at concentrations of 20-40 mg/ml and were stored under nitrogen at -20°C to avoid degradation. Alendronic acid liposomes (L-ALD) were prepared by the thin film hydration (TFH) method as previously described [20,21,25]. DSPC, cholesterol and DSPE-PEG2000 (55:40:5 molar volume) were added to a 25 ml round-bottom flask and 2 ml chloroform/ methanol (4:1 v/v) was added.…”
Section: Preparation Of Liposomesmentioning
confidence: 99%
See 3 more Smart Citations